2004
DOI: 10.1021/ja049130o
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Helicity Inversion by Achiral Anion Stimulus in Synthetic Labile Cobalt(II) Complex

Abstract: The helical chirality of a Co(II) complex with a chiral tetradentate ligand is completely inverted from Lambda to Delta by the addition of achiral NO3- anion as an external stimulus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 35 publications
1
45
0
1
Order By: Relevance
“…These include helical polymers, [1] foldamers, [2] and helical metalc omplexes, [3] whicha re in dynamic equilibrium between the rightand left-handed forms.S ome of them can undergo dynamic helicity inversion upon stimulation by light,h eat, redoxr eaction, pH change,b inding with inorganic or organic species, etc. [7] We have recently reported the dynamic helicityc ontrol of a trinuclearh elical nickel(II) metallocryptand [LNi 3 ]a nd tuning of its helicityinversion rates. Amongt hem, binding with organic species is particularly versatile, because av ariety of chiral and achiral organic species can be used as as timulus to achieve the responsive functions.…”
mentioning
confidence: 99%
“…These include helical polymers, [1] foldamers, [2] and helical metalc omplexes, [3] whicha re in dynamic equilibrium between the rightand left-handed forms.S ome of them can undergo dynamic helicity inversion upon stimulation by light,h eat, redoxr eaction, pH change,b inding with inorganic or organic species, etc. [7] We have recently reported the dynamic helicityc ontrol of a trinuclearh elical nickel(II) metallocryptand [LNi 3 ]a nd tuning of its helicityinversion rates. Amongt hem, binding with organic species is particularly versatile, because av ariety of chiral and achiral organic species can be used as as timulus to achieve the responsive functions.…”
mentioning
confidence: 99%
“…When a racemic Co(II) complex produced with achiral peptide ligands was mixed with a chiral Λ Co(II) analog of the Fe(II) complex, chirality amplification around Co(II) center and in achiral peptide helices were observed via chirality transfer from chiral peptide chains to metal center and to achiral peptide chains. Miyake et al demonstrated that the labile Co(II) complex with a chiral tetradentate ligand containing amide linkages acted as a helicity inversion unit in response to achiral NO3 − anion ( Figure 15) [74,75]. In a solid complex prepared by mixing the chiral ligand and Co(ClO4)2· 6H2O, the Co(II) complex formed the Λ cis-α structure, in which both coordinating nitrogen atoms adopted the (S) configuration.…”
Section: Dynamic Production and Inversion Of Supramolecular Chiralitymentioning
confidence: 99%
“…In contrast, binding of one bidentate NO 3 ¹ anion induces formation of a ¦ isomer as unambiguously characterized by single-crystal X-ray diffraction and CD spectroscopy. 48 This system was further developed to realize peptide helix inversion triggered by an NO 3 ¹ anion. They synthesized a peptidemetal conjugate in which the aforementioned Co helical structures (Figure 6).…”
Section: ç Anion-responsive Metallopeptidesmentioning
confidence: 99%